2003
DOI: 10.1080/1355621031000069855
|View full text |Cite
|
Sign up to set email alerts
|

HIV treatment in drug abusers: impact of alcohol use

Abstract: Studies of alcohol use in HIV-1 infected patients have resulted in conflicting and limited information regarding prevalence, as well as impact on HIV replication, disease progression and response to antiretroviral therapy. Alcohol, drug abuse and past medical information, including antiretroviral treatment, were obtained using research questionnaires and medical chart review in 220 HIV-1 infected drug users. A physical examination was conducted and blood was drawn to evaluate immune measures and nutritional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 9 publications
3
90
1
1
Order By: Relevance
“…Previous studies have shown that among HIV+ individuals with a history of alcohol problems and receiving antiretroviral therapy (ART), alcohol use was associated with lower CD4 counts and either higher or active undetectable HIV viral loads (Miguez et al, 2003;Samet, Horton, Traphagen, Lyon & Freedberg, 2003). In contrast, a recent prospective study found that among HIV+ individuals not receiving ART, heavy alcohol consumption was associated with lower CD4 counts, but no effect on HIV viral load was observed.…”
Section: Alcohol Use and Hiv Infection Disease Progression And Treatmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies have shown that among HIV+ individuals with a history of alcohol problems and receiving antiretroviral therapy (ART), alcohol use was associated with lower CD4 counts and either higher or active undetectable HIV viral loads (Miguez et al, 2003;Samet, Horton, Traphagen, Lyon & Freedberg, 2003). In contrast, a recent prospective study found that among HIV+ individuals not receiving ART, heavy alcohol consumption was associated with lower CD4 counts, but no effect on HIV viral load was observed.…”
Section: Alcohol Use and Hiv Infection Disease Progression And Treatmentioning
confidence: 72%
“…Furthermore, evidence from clinical and laboratory studies has indicated that alcohol abuse may accelerate HIV disease progression (Bagby, Zhang, Purcell, Didier & Nelson, 2006;Hao rah et al, 2004;Miguez, Shor-Posner, Morales, Rodriguez & Burbano, 2003;Samet et al, 2007). In particular, proteasomes and immunoproteasomes, critical immune processes attenuated during progressive HIV-1 infection, are affected by alcohol abuse.…”
Section: Alcohol Use and Hiv Infection Disease Progression And Treatmentioning
confidence: 99%
“…Further, alcoholism comorbidity was an essential concomitant for observation of evidence for neuronal compromise (ie low NAA) and high-energy phosphate metabolism (ie low Cr) in parietal-occipital cortex in individuals with HIV infection. The exceedingly high prevalence of alcoholism in HIV-infected individuals and the interfering effect of alcohol consumption on HIV therapeutic efforts, both in terms of pharmacological response (Miguez et al, 2003) and therapy compliance (Cerwonka et al, 2000;Samet et al, 2004), underscore the relevance of rigorous study of the compounded diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Alcohol, cocaine, and heroin use have all been shown to significantly increase ART non-adherence in patients living with HIV (PLWH). [12][13][14] A meta-analysis of the association between alcohol use and ART adherence found that alcohol use is associated with a 40-50 % decrease in ART adherence.…”
Section: Introductionmentioning
confidence: 99%
“…11 While even Blight^alcohol use (less than once a week) is associated with increased viral loads, there is a dosedependent relationship between alcohol use and nonadherence. 4,11 Similarly, another study found that only 27 % of cocaine users were adherent to their ART regimen. 13 In a nationally representative survey of PLWH, 18 % of patients reported heavy drinking, 40 % reported illicit drug use other than marijuana, and 12 % screened positive for drug dependence.…”
Section: Introductionmentioning
confidence: 99%